BASIC ANALYSES OF DOME FUJI DEEP ICE CORE PART 1 : STABLE OXYGEN AND HYDROGEN ISOTOPE RATIOS, MAJOR CHEMICAL COMPOSITIONS AND DUST CONCENTRATION - ワタナベ, オキツグ; フジイ, ヨシユキ; カミヤマ, コキチ; モトヤマ, ヒデアキ; フルカワ, テルオ; イガラシ, マコト; コウノ, ミカ; カナモリ, サトル; カナモリ, ノブコ; アゲタ, ユタカ; ナカオ, マサヨシ; タナカ, ヒロシ; et al. (National Institute of Polar Research, 1999)
P(論文) Basic chemical analyses of a 2503m deep ice core obtained at Dome Fuji Station, Antarctica in 1995-1996 were carried out to determine stable oxygen and hydrogen isotope ratios, major chemical compositions and microparticle concentrations. We here describe the analytical procedure and the results as well as the determination of working time scale. The ice core covers the past 340ka which includes three glacial-interglacial cycles clearly shown by the stable oxygen isotope profile. Major chemical compositions and microparticle concentrations larger than 0.52μm show high concentrations in glacials and low in interglacials. departmental bulletin paper